The myolymphangioplasty in breast cancer - Mañana, Julio; Guicheff, Vladimir (Cirugía del Uruguay, 2020)
Nine cases of miolinfangioplastia with latissimus dorsi, performed in an attempt to prevent postoperatory edema of the upper limb on the same side as the mammary resection, are presented. Distant results obtained by the use of this teclinique can be considered good, and we advise their application in radical mastectomy.